EVALUATION OF THE POSSIBILITIES OF REVITALIZATION OF THE AUCIEMA FARM IN THE DEGRADED AREA - Upmane, Sintija; Matisovs, Ivars (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2023)
Title article “Evaluation of the possibilities of revitalization of the Auciems farm in the degraded territory” The aim of the article is to survey the information about the degraded territory of the former Auciems village farm, to assess their current condition, to evaluate the possibilities of restoration and to offer a possible alternative for cleaning up the territory. During the development of the article, the concept of brownfields and the causes of their formation were considered. An on-site assessment of the condition of the facility was surveyed.